The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1109/access.2021.3139312
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall Prediction Using Machine Learning Algorithms for the Various Ecological Zones of Ghana

Abstract: Accurate rainfall prediction has become very complicated in recent times due to climate change and variability. The efficiency of classification algorithms in rainfall prediction has flourished. The study contributes to using various classification algorithms for rainfall prediction in the different ecological zones of Ghana. The classification algorithms include Decision Tree (DT), Random Forest (RF), Multilayer Perceptron (MLP), Extreme Gradient Boosting (XGB) and K-Nearest Neighbour (KNN). The dataset, cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The RMSE of 2.7 mm and an MAE of 8.8 mm were obtained in their study. Rainfall prediction in Ghana's several ecological zones was shown to be better predicted using XGBoost, RF, and MLP, according to Appiah-Badu et al [60]. The study by Lawal et al [65] found XGBoost as the best model with an MAE of 0.042529 and RMSE of 0.05654 in predicting daily rainfall in the Nyando region of Kenya.…”
Section: E Comparative Analysis Of Xgboost With Existing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RMSE of 2.7 mm and an MAE of 8.8 mm were obtained in their study. Rainfall prediction in Ghana's several ecological zones was shown to be better predicted using XGBoost, RF, and MLP, according to Appiah-Badu et al [60]. The study by Lawal et al [65] found XGBoost as the best model with an MAE of 0.042529 and RMSE of 0.05654 in predicting daily rainfall in the Nyando region of Kenya.…”
Section: E Comparative Analysis Of Xgboost With Existing Methodsmentioning
confidence: 99%
“…Notably, the results illustrate how the corresponding approach performs in terms of MAE and RMSE on test set performance. [54], [58], [60]. Consequently, 20% of data was drawn from Kenya weather station and another 20% from Tanzania.…”
Section: A Evaluating Xgboostmentioning
confidence: 99%
“…Rainfall prediction is one of the widely studied areas in this context. The proposed study in [13] was used to classify the rainfall status as yes or no in different zones of Ghana considering various climatic features that were collected between the years 1980 and 2019. Well-known classification algorithms, including the decision tree (DT), multilayer perceptron (MLP), KNN, RF, and extreme gradient boosting (XGBoost) were applied for this aim.…”
Section: Introductionmentioning
confidence: 99%
“…For this goal, several machine learning algorithms have been investigated, each with its own set of strengths and applications. For example, artificial neural networks (ANN) [22,23], recurrent neural networks (RNN) [24,25], random forest (RF) [26], gaussian process regression (GPR) [27], gradient-boosting [28], extreme gradient boosting [29], and long-short term memory (LSTM) [30].…”
Section: Introductionmentioning
confidence: 99%